Brief Report: Association of Elevated Adipsin Levels With Pulmonary Arterial Hypertension in Systemic Sclerosis. Issue 10 (27th September 2017) - Korman, Benjamin D.; Marangoni, Roberta Goncalves; Hinchcliff, Monique; Shah, Sanjiv J.; Carns, Mary; Hoffmann, Aileen; Ramsey‐Goldman, Rosalind; Varga, John
Abstract : Objective: Adipose tissues secrete adipokines, peptides with potent effects modulating fibrosis, inflammation, and vascular homeostasis. Dysregulated adipose tissue biology and adipokine balance have recently been implicated in systemic sclerosis (SSc). This study was undertaken to determine whether altered circulating adipokine levels correlate with SSc disease subsets or clinical manifestations. Methods: Multiplex assays were used to measure circulating adipokine levels in 198 patients with SSc and 33 healthy controls. Data were evaluated for correlations between serum adipokine levels and demographic and clinical features, including pulmonary arterial hypertension (PAH). To assess the relevance of adipsin, an adipokine involved in complement pathway activation, in SSc, we analyzed publicly available genetic and transcriptomic data. Results: Levels of adiponectin and adipsin differed significantly between controls and patients. Adipsin was significantly elevated in patients with limited cutaneous SSc (odds ratio [OR] 28.3 [95% confidence interval (95% CI) 7.0–113.8]; P  < 0.0001), and its levels were associated with serum autoantibody status, pulmonary function and cardiovascular parameters, and PAH (OR 3.3 [95% CI 1.3–8.7]; P  = 0.02). Elevated adipsin was more strongly associated with PAH than B‐type natriuretic peptide was. Moreover, in SSc patients, adipsin gene single‐nucleotide polymorphisms were associated with PAH. Transcriptome data set analysis demonstrated elevated adipsin expression in patients with SSc‐related PAH. Conclusion: We identify adipsin as a novel adipose tissue–derived marker of SSc‐related PAH. Circulating adipsin levels might serve as predictive biomarkers in SSc. Mechanistically, adipsin might represent a pathogenic link between adipocyte dysfunction and complement pathway activation and play an important role in the pathogenesis of SSc‐related PAH.